Umbilical Cord Blood Transplants: Current Status and Evolving Therapies - Gupta, Ashish O.; Wagner, John E. (Frontiers in Pediatrics, 2020)
Hematopoietic cell transplants using stem cells from umbilical cord blood are used worldwide for treatment of malignant and non-malignant disorders. Transplant outcomes from this stem cell source has shown promising outcomes in successfully treating various hematologic, immunologic, malignant and inherited metabolic disorders. Rapid availability of these stem cells is an important advantage over other unrelated donor transplants, especially in situations where waiting can adversely affect the prognosis. Umbilical cord blood is rich in CD34+ stem cells though with a limited cell dose and usually takes longer to engraft. Limitations around this have been addressed by in-vivo and ex-vivo expansion techniques as well as to enhance engraftment kinetics. Development of adoptive immunotherapy using other components of umbilical cord blood such as regulatory T-cells, virus specific T-cells and natural killer cells has further transformed the field and enhanced the utility of umbilical cord blood unit.